Neutron activation as benchmark for cross section evaluations: Demonstration through the MACS of 50Cr for nuclear technology applications - P. Pérez-Maroto; C. Guerrero; B. Fernández; A. Casanovas-Hoste; M.E. Stamati (Physics Letters B, 2025)
Neutron cross section libraries often differ with each other due to the limited availability of differential cross section data from time-of-flight experiments. These are indeed challenging, requiring state-of-the-art facilities and detectors, as well as an involved data analysis. However, in some cases, an easier alternative can be found in simpler integral experiments, as it is demonstrated herein. The capture cross section of 50Cr plays an important role in nuclear reactors and recent criticality safety benchmarks pointed to an increase of 20%, which has been incorporated in the recent INDEN (2023) evaluated library. In this work we have carried out an epithermal neutron activation measurement on 50Cr at the CNA HiSPANoS facility. The resulting Maxwellian Average Cross Section (MACS) at 30 keV, 37.1(20) mb, provides enough evidence to discard the proposed increase in the cross section. Furthermore, it illustrates the suitability of the activation technique to benchmark cross section evaluations in the epithermal energy region. This can in principle be extended to other reactions (as far as they result in radioactive nuclei) and to the fast neutron range by employing mono-energetic beams from D-D and D-T reactions in similarly simple experiments.